Análise estrutural de edifício alto submetido às pressões flutuantes induzidas pela ação do vento - Ena Sosa Chavez (2006)
In this work are analyzed the displacements, accelerations and forces in a tall building under influence of the random wind loading by means of dynamic analysis in time domain.The simulation of the turbulent wind effect is made by considering the statistical characteristics related to the nature of wind and the parameters dependent on surface roughness of the terrain. The evaluation of structural behavior is done through the computer program ANSYS based on the finite element method. Wind loadings are obtained by superposition of harmonic functions consistent with an adopted spectrum of wind and the technique of Monte Carlo is applied for statistical evaluation of responses.The results thus obtained are compared with results using the recommendations of the Brazilian standard NBR6123:1988 and the users comfort levels are evaluated based on the indices of human perception of accelerations.